Associations between cognitive–personality traits and perceptual responses during low-volume high-intensity interval exercise in overweight-to-obese adults - Zhang, Ruohan; Sun, Jingyuan; Gu, Jinfa (Frontiers in Psychology, 2026)
BackgroundLow-volume high-intensity interval exercise (Lv-HIIE) has been proposed as a time-efficient, effective training approach for adults with overweight or obesity. However, its perceptual tolerability may depend on cognitive–personality traits influencing emotional and exertional regulation. This study examined how these traits relate to perceptual responses during Lv-HIIE.MethodsThirty-two physically inactive adults (BMI = 28.21 ± 2.93 kg·m2; 11 males, 21 females; age = 28.3 ± 4.9 years) completed a 10-week Lv-HIIE program of 30 supervised sessions. Perceptual measures of affective valence, arousal, perceived exertion, recovery, and enjoyment were collected in every session, and data from the 1st, 15th, and 30th sessions were analyzed as representative points. Goal orientation and personality hardiness were assessed before the intervention, and Pearson’s correlations examined associations between perceptual responses and cognitive–personality variables.ResultsAcross the intervention, affective valence showed strong negative correlations with heart rate and perceived exertion, and positive correlations with enjoyment (r = −0.82 to −0.66, p < 0.01). Goal orientation and hardiness were moderately to strongly associated with higher affective valence (r = 0.59–0.65) and greater enjoyment (r = 0.38–0.56), while correlating negatively with perceived exertion (r = −0.38 to −0.56). These associations became progressively stronger toward later sessions, indicating adaptive affective regulation and enhanced psychological tolerance with repeated Lv-HIIE exposure.ConclusionIndividuals with higher goal orientation and greater hardiness exhibited more positive affective and enjoyment responses together with lower perceived exertion. Overall, these findings suggest that cognitive–personality traits contribute to perceptual and affective regulation during high-intensity exercise.